Digital Photographs in Analysis of Lip Prints for Gender Identification - Poudel, Pratibha; Srii, Ritesh; Mahanta, Swagat Kumar (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Introduction: Cheiloscopy is considered as an emerging method in forensic odontology for identification of gender. There are several methods given in literature to identify the lip print types. Digital photographs can be used to study the lip prints for gender identification. Objective: The aim of the study was to identify the predominant lip print pattern in males and females by using digital photographs. Methods: This analytical cross-sectional study included 206 subjects, comprising 103 males and 103 females. Digital photographs were used to identify the lip print patterns. The classification given by Suzuki and Tsuchihashi was used to further classify the lip patterns. Kappa test was applied to check for inter observer variation. Statistical analysis was done using SPSS version 23. The association between gender and lip print type was tested by Chi square test. Results: Type I was the most common lip print followed by Type I’. Type V was the least common lip print followed by Type IV. Type I and Type II were the most common pattern in females and males respectively and these differences were found to be statistically significant (p<0.01). Conclusion: Digital photographs are very useful for identification of lip print pattern. The variation in lip print pattern among males and females can be taken as an aid in gender determination.